Optimalisasi Potensi Wisata Alam Curug Gribik dan Gubug Serut Untuk Mendorong Pembangunan Berkelanjutan di Kelurahan Sekaran Gunungpati - Salsabila Fatin Maulida Rahma; Dwimei Ayu Dewandari P (Karya Nyata : Jurnal Pengabdian kepada Masyarakat, 2024)
Sekaran Village has enormous tourism potential thanks to its unique natural conditions. However, this potential has not been utilized optimally by society. This research aims to optimize the natural tourism potential of Curug Gribik and Gubug Serut in Sekaran Village in order to encourage sustainable economic development. Through a qualitative approach, this research explores community perceptions and participation in the development of these two tourist attractions. By involving the community directly, it is hoped that effective strategies can be found to increase awareness of the importance of conservation and optimize the economic potential of the tourism sector. The results of this research show that with the right approach and active community participation, the potential for natural tourism in Sekaran Village can be developed into a sustainable source of income and improve community welfare